POSSIBILITY OF MATRIX REPRESENTATION OF BASIC UNARY OPERATIONS ON GRAPHS - Якімова, Наталія (SWorldJournal, 2025)
Today, science is faced with an increasing number of problems related to computerization. It is the needs of computer information processing that require the study of the possibilities of matrix representation of graphs and, as a result, matrix representa